(untitled) (Bangladesh Journal of Botany, 2025)
This study investigated the ecotoxicological effects of lead (Pb) and cadmium (Cd) stress, both individually and in combination, on spinach (Spinacia oleracea), by analyzying the growth characteristics, antioxidant responses, and photosynthetic damage mechanisms of spinach under controlled experimental conditions with different concentration gradients. Pb-Cd combined stress significantly inhibited spinach biomass, with a dose-dependent and synergistic enhancement, with the total dry weight decreasing by up to 62.8%. The root system was the primary target of stress, with dry weight loss (minimum 28.4% in control) being significantly higher than that of the aerial parts. The biomass differences between stems and leaves were closely associated with the differential antioxidant capacity of the organs. At low concentrations, the increase in leaf superoxide dismutase (SOD) activity (by 12.3-18.5%) partly alleviated oxidative damage, while a sharp increase in peroxidase (POD) activity in the roots (3.8-fold at Pb200 + Cd20) revealed a lignin-mediated cell wall reinforcement mechanism. The antioxidant system responded with a dynamic threshold effect: at low concentrations (Pb50/Cd5), SOD activity significantly increased (421.5 U/g FW), triggering primary defense, whereas at high concentrations (Pb200/Cd20), enzyme activity decreased to 382.4 U/g FW. Cd exerted a more pronounced destructive effect on chlorophyll a (decrease by 56.3%) compared to Pb (34.7%), with the mechanism involving chloroplast structural damage and Mg2+ competition inhibition. Combined stress, through a synergistic pathway (Cd inhibition of synthetase activity, Pb acceleration of pigment degradation), reduced chlorophyll a content to only 28.9%. This study quantifies the physiological tolerance thresholds of spinach to Pb-Cd combined stress and reveals a coupled mechanism of ’heavy metal interaction-antioxidant hierarchical response-photosynthetic damage synergy’, providing a theoretical basis for ecological risk assessment of polluted farmland and safe spinach production. Bangladesh J. Bot. 54(3): 855-864, 2025 (September) Special